1 Move the negative sign to the left.
(
9
x
)
1
2
8
x
−
1
2
3
(9x)
2
1
3
√
8x
−
2
1
2 Convert
(
9
x
)
1
2
(9x)
2
1
to square root.
9
x
8
x
−
1
2
3
√
9x
3
√
8x
−
2
1
3 Use this rule:
a
b
=
a
b
√
ab
=√
a
√
b
.
9
x
8
x
−
1
2
3
√
9
√
x
3
√
8x
−
2
1
4 Since
3
×
3
=
9
3×3=9, the square root of
9
9 is
3
3.
3
x
8
x
−
1
2
3
3√
x
3
√
8x
−
2
1
5 Use Multiplication Distributive Property:
(
x
y
)
a
=
x
a
y
a
(xy)
a
=x
a
y
a
.
3
x
8
3
x
−
1
2
3
3√
x
3
√
8
3
√
x
−
2
1
6 Calculate.
3
x
×
2
x
−
1
2
3
3√
x
×2
3
√
x
−
2
1
7 Use this rule:
(
x
a
)
b
=
x
a
b
(x
a
)
b
=x
ab
.
3
x
×
2
x
−
1
2
×
3
3√
x
×2x
2×3
−1
8 Simplify
2
×
3
2×3 to
6
6.
3
x
×
2
x
−
1
6
3√
x
×2x
6
−1
9 Move the negative sign to the left.
3
x
×
2
x
−
1
6
3√
x
×2x
−
6
1
10 Use Negative Power Rule:
x
−
a
=
1
x
a
x
−a
=
x
a
1
.
3
x
×
2
×
1
x
6
3√
x
×2×
6
√
x
1
11 Use Quotient Rule:
x
a
x
b
=
x
a
−
b
x
b
x
a
=x
a−b
.
\[3\times 2\sqrt[2}-\frac{1}{6]{x}\]
12 Simplify
1
2
−
1
6
2
1
−
6
1
to
1
3
3
1
.
3
×
2
x
3
3×2
3
√
x
13 Simplify.
6
x
3
6
3
√
x